Reducing the Water Hardness by Using Electromagnetic Polarization Method - Abdulrazzaq, Ghassan Hassan (Al-Khwarizmi Engineering Journal, 2017)
Hard water does not pose a threat to human health but may cause precipitation of soap or results stone in the boilers. These reactions are caused by the high concentrations of Ca and Mg. In the industry they are undesirable because of higher fuel consumption for industrial use .Electromagnetic polarization water treatment is a method which can be used for increasing the precipitation of Ca 2+ and CO3 2- ions in hard water to form CaCO3 which leads to decrease the water hardness is research has been conducted by changing the number of coil turns and voltage of the system. The spectroscopy electron microscope was used for imaging the produced crystals. Results of the investigation indicated that the electromagnetic polarization can be used in precipitation to decrease the hardness of water due to increase in the precipitation percent of CaCO3.